Temperature vs depth profile at heat flux station HF1765 of RV MARIA S. MERIAN cruise MSM69 - Heinrich Villinger; Ingo Grevemeyer; Norbert Kaul; Satish C Singh (PANGAEA, 2025)
The heat flux measurements presented in this report were made during expedition MSM69 on the German research vessel RV Maria S. Merian (November 14, 2017 to December 22, 2017). A total of 69 heat flux measurements (profile HF1760 to profile HF1767) were successfully carried out colocated with the iLAB reflexion seismic profile. The aim of the measurements was to investigate whether low-temperature hydrothermal fluids diffuse at the seafloor where the oceanic basement is not covered by sediments. While low heat flux measurements clearly show that cold seawater enters the subsurface, no diffuse leakage of hydrothermal fluids could be detected at any location.
In: Villinger, H et al. (2025): Marine heat flux measurements of RV MARIA S. MERIAN cruise MSM69 [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.980610